Development of Genially-Based BAHARI Learning Media for Enhancing Arabic Speaking Skills - Mukhtar Ishak Miolo; Nicky Befli Lasanggo; Damhuri; Ratni Bt. Hj. Bahri; Suharia Sarif (Al-Muyassar: Journal of Arabic Education, 2026)
This study aims to develop and evaluate BAHARI (Bahasa Arab Interaktif), a Genially-based interactive multimedia designed to enhance students’ speaking skills (maharah al-kalam) at MA Al-Huda, Gorontalo City. This research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The novelty of this study lies in the development of an interactive animation-based Arabic learning medium using the Genially platform specifically designed for speaking skill acquisition and aligned with the KMA No. 183 of 2019 curriculum. Data were collected through interviews, observations, expert validation, and pre-test–post-test assessments. Validation by four experts (media, material, language, and audio-linguistics) yielded an average feasibility score of 99% (excellent), indicating high pedagogical, technical, and linguistic quality. The results revealed a significant improvement in students’ speaking performance, with mean scores increasing from 33.18 to 69.09 (p < 0.05), thereby answering the research problem regarding the effectiveness of digital interactive media in improving maharah al-kalam. The findings demonstrate that the integration of animation, narration, and interactivity enhances learners’ motivation, pronunciation accuracy, and oral fluency. Theoretically, this study contributes to the development of multimedia-based Arabic learning models, while practically offering an effective and engaging digital resource to support communicative competence in classroom settings.